trans-Iodido(pyrazinyl-κC (2))bis(triphenylphosphane-κP)palladium(II) - Tu, Yao-Jen (International Union of Crystallography, 2012)
There are two independent molecules with similar configurations in the asymmetric unit of the title complex, [Pd(C(4)H(3)N(2))I(C(18)H(15)P)(2)]. In each molecule, the geometry around the Pd atom is distorted square-planar, with the Pd atom displaced by 0.0549 (12) and 0.0734 (13) Å from the least-squares plane of the I—P—P—C atoms. The PPh(3) ligands are in trans positions, with P—Pd—P angles of 173.12 (4) and 170.29 (4)°, while the pyrazinyl ligands and I atoms, also trans to each other, form C—Pd—I angles of 179.38 (12) and 178.44 (12)°. In the crystal, C—H⋯π interactions occur, resulting in a three-dimensional supramolecular architecture.